CHANGES OF COAGULATION IN MEN AND WOMEN WITH ACUTE CORONARY SYNDROME WITH ST SEGMENT ELEVATION - N.V. Netyazhenko (Bogomolets National Medical University, 2015)
The article describes the results of a studyof hemostasis in women with acute coronary syndrome(ACS) with ST-segment elevation compared to men. 105patients were examined, 45 of whom were women, On ascale TIMI patients of both sexes were divided into threegroups. The I group consisted of 15 women and 20 menwith a risk of mortality <1% in group II - 15 women and 18men with a risk of 1 to 4%, and 15 women and 22 men werethe group III with the risk of ≥4%. The groups werecomparable. Research methods plasma coagulationhemostasis included the following tests: activated partialthromboplastin time (APTT), thrombin time (PT), fibrinogenconcentration, the amount of soluble fibrin monomercomplexes, while XIIa dependent fibrinolysis. Forlaboratory evaluation level of natural inhibitors of bloodcoagulation following methods were used: determinationof the activity of antithrombin III and protein C by achromogenic substrate. Increased risk of mortality within30 days in ACS scale T²M² associated with the deepeningof gender differences in hemostasis, which are mostpronounced in high and very high risk. Simultaneousdetection of hypercoagulation shifts in a shortening of theaPTT and PT in the high-risk group of women next todecreased activity of antithrombin III and protein C in themoderate and high risk disclose a violation of the balanceof procoagulants with the major components ofanticoagulant and fibrinolytic systems in womencompared with men ACS segment elevation ST.